2019
DOI: 10.1038/s41598-019-56084-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal-organic Framework-driven Porous Cobalt Disulfide Nanoparticles Fabricated by Gaseous Sulfurization as Bifunctional Electrocatalysts for Overall Water Splitting

Abstract: Both high activity and mass production potential are important for bifunctional electrocatalysts for overall water splitting. Catalytic activity enhancement was demonstrated through the formation of CoS2 nanoparticles with mono-phase and extremely porous structures. To fabricate porous structures at the nanometer scale, Co-based metal-organic frameworks (MOFs), namely a cobalt Prussian blue analogue (Co-PBA, Co3[Co(CN)6]2), was used as a porous template for the CoS2. Then, controlled sulfurization annealing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Nevertheless, the bottleneck limitations such as poor stability, high cost of well-known commercial (Pt and Ir-based) catalysts, and poor performance of earth-abundant materials limit its real-time applications. Hence, the rational design of a bifunctional electrocatalyst for real-time water electrolysis under general pH conditions with excellent performance and superior stability is the need of the hour for sustained green energy technologies. In particular, Nickel and Cobalt based electrocatalyst holds prominent characteristics like corrosion resistance, efficient electron transport, and an eco-friendly nature, which paves the way to use Ni and Co in a redox reaction as an excellent electrocatalyst in alkaline and neutral pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the bottleneck limitations such as poor stability, high cost of well-known commercial (Pt and Ir-based) catalysts, and poor performance of earth-abundant materials limit its real-time applications. Hence, the rational design of a bifunctional electrocatalyst for real-time water electrolysis under general pH conditions with excellent performance and superior stability is the need of the hour for sustained green energy technologies. In particular, Nickel and Cobalt based electrocatalyst holds prominent characteristics like corrosion resistance, efficient electron transport, and an eco-friendly nature, which paves the way to use Ni and Co in a redox reaction as an excellent electrocatalyst in alkaline and neutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, metal–organic Frameworks (MOFs) were significantly studied for numerous environmental and energy-related applications, including sensing, gas storage and separation, catalysis, drug delivery, optoelectronics, magnetism, and fluorescence. , Typically, MOF is a coordinate network of metal ions and organic ligands with the potential to form various nanostructures. , Fascinatingly, tailored compositions, porous structure, and the crystalline nature of MOF make them promising catalysts with excellent chemical and mechanical properties, definite surface areas, tunable pore formations, and functionalities …”
Section: Introductionmentioning
confidence: 99%
“…First, the OER performance of the NiFe LDH-based electrocatalysts was measured as the overpotential at a current density of 10 mA cm −2 , which is generally used as a reference to evaluate electrocatalysts. 13,46 Fig. 4(a) displays the polarization curves of the OER for each electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, improving the electrocatalytic performance of the OER would effectively improve water splitting performance. 13,21 Although OER electrocatalysts for use under alkaline conditions commonly contain noble metals, such as Ir and Ru, noble metals present disadvantages such as supply shortages and exhaustion, high cost, and limitations in applications requiring mass production. 12,16,22 For this reason, electrocatalysts based on earth-abundant elements, such as transition metal oxides, layered double hydroxides (LDHs), sulfides, single atom catalysts (SACs), two-dimensional materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The uniformly porous MOF-derived CoS 2 exhibited better electrochemical performance in the WS reaction, with the applied operating OER reaction potential of 298 mV @ 10 mA cm −2 . 57 On the other hand, the sulfide-supported metallic monoclinic 1T phase MoS 2 electrocatalyst was designed through an accessible two-step solvothermal method, followed by hydrolysis. The suggested that the 1T-MoS 2 electrocatalyst holds promising catalytically active sites, fast mass transport properties, and fascinating energy efficiency for the energy storage system.…”
Section: Metal Sulfide-based Electrocatalystsmentioning
confidence: 99%